ASSOCIATION BETWEEN PHASE ANGLE AND BASAL METABOLIC RATE IN BRAZILIAN ELDERLY MEASURED BY BIOIMPEDANCE: A CROSS-SECTIONAL OBSERVATIONAL STUDY (CIPEEX, 2026)
Aging leads to changes in body composition that impact metabolism and functionality. Among the markers derived from bioelectrical impedance analysis (BIA), the phase angle (PhA) has been proposed as an indicator of cellular integrity and a potential predictor of metabolic outcomes. This study aimed to characterize PhA in a large sample of older Brazilian adults and investigate its association with basal metabolic rate (BMR). A cross-sectional observational study was conducted using tetrapolar BIA applied according to a standardized protocol, with data collected between 2020–2024 in different Brazilian states, with greater representation from the Southeast, South, and Central-West regions. A total of 289 individuals aged ≥60 years were included. Exclusion criteria comprised implanted electronic devices, acute conditions that could interfere with BIA, and severe cognitive impairment. One-way ANOVA was used to compare PhA across age groups, and linear regression was used to examine the impact of PhA on BMR. A significant age-related effect was observed for PhA (F(9, 2005) = 21.01; p < 0.0001), with progressively lower values from the age of 70 onwards and notable post-hoc differences between 66 vs. 70 years (p = 0.0149), 66 vs. 71 (p = 0.0009), and 66 vs. 74 (p < 0.0001). PhA was a significant, albeit weak, predictor of BMR in an age-weighted sample (R² = 0.090; F(1, 2614) = 21.135; p < 0.001). In conclusion, PhA declines with age and explains a small portion of the variability in BMR, supporting its use as a complementary marker in metabolic and functional assessment panels for older adults. This motivates the need for longitudinal studies to elucidate causality and refine predictive models.
Keywords: elderly; body composition; bioelectrical impedance; skeletal muscle mass